Pelatihan Minat dan Bakat untuk Memasuki Dunia Kerja di Era Pandemi pada Komunitas PKK “Candi Losmen” Kota Semarang - Constantinus Constantinus; Dian Wishnu Brata (Perkumpulan Kualitama Edukatika Indonesia, 2022)
The purpose of this activity is to provide information related to interests and talents to enter the world of work in the pandemic era to PKK members in Semarang City. The partner in this PKM is PKK “Candi Losmen” in Semarang City, which consists of 25 housewives. The problem faced by partners is the obstacle of career assistance for children according to their interests and talents. This is because so far the assistance provided is still in the form of providing job vacancies. Children are considered vulnerable to having career problems in the world of work, because most of them work not based on their interests and talents, but only because they fill existing job vacancies. In fact, many children experience difficulties in their careers, it is because they feel that work is a burden for life, not a self-actualization of their interests and talents. Career mentoring can be a solution for mothers as parents in helping their children determine career direction. Career mentoring is not only limited to hard skills but also soft skills where children are guided to be able to better recognize their talents and interests and can be empowered to support their careers in the future. The results of the PKM implementation are also expected to be able to produce the output of teaching materials in the form of lecture papers, and publication articles in online media.